F7 gene variants modulate protein levels in a large cohort of patients with factor VII deficiency - Quintavalle, Gabriele; Riccardi, Federica; Rivolta, Gianna Franca; Martorana, Davide; Di Perna, Caterina; Percesepe, Antonio; Tagliaferri, Annarita; on behalf of the Ad-Hoc Study Group (Thrombosis and Haemostasis, 2017)
Congenital factor VII (FVII) deficiency is a rare bleeding disorder caused by mutations in F7 gene with autosomal recessive inheritance. A clinical heterogeneity with poor correlation with FVII:C levels has been described. It was the objective of this study to identify genetic defects and to evaluate their relationships with phenotype in a large cohort of patients with FVII:C<50%. One hundred twenty-three probands were genotyped for F7 mutations and three polymorphic variants and classified according to recently published clinical scores. Forty out of 123 patients (33?%) were symptomatic (43 bleedings). A severe bleeding tendency was observed only in patients with FVII:C<0.10%. Epistaxis (11%) and menorrhagia (32% of females in fertile age) were the most frequent bleedings. Molecular analysis detected 48 mutations, 20 not reported in the F7 international databases. Most mutations (62%) were missense, large deletions were 6.2%. Compound heterozygotes/homozygotes for mutations presented lower FVII:C levels compared to the other classes (Chi2=43.709, p<0,001). The polymorphisms distribution was significantly different among the three F7 genotypic groups (Chi2=72.289, p<0,001). The presence of truncating mutations was associated with lowest FVII:C levels (Chi2=21.351, p=0.002). This study confirms the clinical and molecular variability of the disease and the type of symptoms. It shows a good correlation between the type of F7 mutation and/or polymorphisms and FVII:C levels, without a direct link between FVII:C and bleeding tendency. The results suggest that large deletions are underestimated and that they represent a common mechanism of F7 gene inactivation which should always be investigated in the diagnostic testing for FVII deficiency.
Keywords: Bleeding score; factor VII deficiency; gene deletion; genotype; phenotype